Chemical composition of the leaf oil of Annona muricata L. from Nghe An - Dai, Do Ngoc; Thang, Tran Dinh; Dung, Nguyen Xuan (Academia Journal of Biology, 2014)
The leaf oil of Annona muricata L. collected from Vinh city, Nghe An province, Vietnam, in May 2006 was isolated by steam distillation to give oil yield 0.1% and analyzed by Capillary GC and GC/MS. Sixty components have been identified accounting more than 95.1% of the oil respectively. The major constituents of this oil appeared to be b-pinene (27.6%) vµ bicyclogermacrene (13.7%) vµ germacrene D (11.3%). Less predominant constituents included a-pinene (7.7%), limonene (4.8%), myrcene (3,3%), calacorene (3.1%), b-bourbonene (3.0%), 3-oxo-p-menth-1-en-7-al (2.9%), b-elemene (2.8%), a-amorphene (2.7%),a-terpinolene (2.2%), a-copaene (1.8%), bicycloelemene (1.4%), spathoulenol (1.2%), (Z)-b-ocimene (1.2%). All the other components were in concentration of less than 0.1-0.9%.